DEVELOPMENT MATH PROBLEM CARDS BASED ON LOCAL WISDOM - Abdul Jabar; Winda Agustina; Rahmita Yuliana Gazali; Linda Windi Sindi Yana; Norsifah Norsifah (Proceeding International Conference on Digital Education and Social Science, 2022)
Mathematics has been studied by someone since childhood, so mathematics is almost daily learn by students. However, the context of mathematics subject is still general. Likewise, the practice questions or tests given are still glued to general textbooks. Elements of culture and local wisdom that are close to the student's environment are still rarely applied in schools. Whereas the scope of local wisdom is very broad so it is very possible to be a context for learning mathematics. Thus, it is hoped that students can more easily understand mathematics in the context of local wisdom that is close to their daily lives. This is in line with the government's policy in the “Kurikulum Merdeka”, teachers should make the surrounding environment a source of learning. The purpose of this study was to develop a math problem cards based on local wisdom in Marabahan, Barito Kuala Regency. The scope of this research is the evaluation of mathematics learning. The research method uses R&D with a 4D development model. The research subjects were fourth grade students. The object of the research is a math problem card based on local wisdom. The data collection instrument used a validity sheet, a practicality sheet, and a student response questionnaire sheet. The data analysis technique uses averages and percentages. This research produces a math problem card based on local wisdom on geometry material, namely triangles and quadrilaterals. The developed math problem cards meet the valid and practical criteria, and get Excellent student responses.